The Role of Intrinsic Motivation as a Mediating Influence of Organizational Culture and Self-Efficacy on Employee Productivity at PT Jasa Raharja Bali Branch in Denpasar - Made Deda PURWANTINI; Ida Bagus Udayana PUTRA; A.A. Media MARTADIANI (International Journal of Environmental, Sustainability, and Social Science, 2025)
Human resources (HR) plays a strategic role in achieving company goals, especially in the public service sector, such as PT Jasa Raharja. This study analyzes the influence of organizational culture and self-efficacy on productivity and intrinsic motivation, with a population of all PT Jasa Raharja Bali Branch employees in Denpasar. The sample used was a saturated sample of 51 respondents. The data collection method is a questionnaire. The analysis technique used to answer the hypothesis is inferential analysis using Partial Least Square (PLS). The results of the study indicate that organizational culture does not have a significant effect on employee productivity and intrinsic motivation. On the contrary, self-efficacy has a significant positive effect on both. Intrinsic motivation also has a positive effect on productivity but is only able to mediate the relationship between self-efficacy and productivity, not between organizational culture and productivity. Based on the Theory of Reasoned Action (TRA), individual behavior is influenced by subjective attitudes and norms. Although the organizational culture at PT Jasa Raharja Bali is quite good, its impact on productivity has not been felt because employee attitudes are not positive enough and social pressure to implement them is weak. On the other hand, self-efficacy and intrinsic motivation are closely related to these attitudes and norms. Employee self-confidence in completing tasks can strengthen positive attitudes and increase work motivation.